2009
DOI: 10.1002/jhm.526
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient thromboprophylaxis use in U.S. hospitals: Adherence to the seventh American College of Chest Physician's recommendations for at‐risk medical and surgical patients

Abstract: Few medical and surgical patients at high risk of VTE receive appropriate inpatient prophylaxis in accordance with guideline recommendations. It is important for individual hospitals to improve VTE prophylaxis practices to meet national performance initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 17 publications
(21 reference statements)
3
30
2
Order By: Relevance
“…Despite the recommendation, there remain a significant proportion of individuals who underwent orthopedic surgery but who were not prescribed prophylactic measures. A study of 188 800 surgical discharge records during [2005][2006] found that approximately 20% of surgery patients did not receive VTE prophylaxis during hospitalization [25]. Another study found that only 19% of persons undergoing knee or hip replacement surgery received postdischarge anticoagulant therapy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recommendation, there remain a significant proportion of individuals who underwent orthopedic surgery but who were not prescribed prophylactic measures. A study of 188 800 surgical discharge records during [2005][2006] found that approximately 20% of surgery patients did not receive VTE prophylaxis during hospitalization [25]. Another study found that only 19% of persons undergoing knee or hip replacement surgery received postdischarge anticoagulant therapy [26].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 75.1% of at-risk cancer patients did not receive any anticoagulation during their hospital stay. There appear to be differences in the use of prophylaxis in surgical compared with medical hospitalized cancer patients, with a trend toward higher rates of prophylaxis in surgical patients with cancer [25,44,57,59]. In a study by Amin et al [57] of 30,124 surgical and 42,213 medical cancer hospitalized patients, the overall rate of any pharmacologic or mechanical prophylaxis given was 69.6 and 42.2%, respectively.…”
Section: Gaps In the Provision Of Vte Prophylaxis In The Cancer Patiementioning
confidence: 94%
“…Despite the established increased risk of VTE in the cancer patient population and the availability of evidencebased guidelines recommending thromboprophylaxis, several studies have demonstrated that VTE prophylaxis is underutilized in at-risk cancer patients (Table 5) [38,41,44,[54][55][56][57][58][59][60][61][62][63]. In a recent retrospective study, inpatient, outpatient, and discharge databases were queried for anticoagulant use between January 2005 and December 2007 to assess VTE prophylaxis patterns across the continuum of care in 2,544 medical cancer patients at risk of VTE according to 2008 ACCP guidelines [60].…”
Section: Gaps In the Provision Of Vte Prophylaxis In The Cancer Patiementioning
confidence: 99%
“…A number of studies [20][21][22][23][24] illustrate that hospitalized medical patients frequently do not receive ''appropriate'' prophylaxis (defined as appropriate dose, type, and duration). In addition, many patients do not meet VTE prophylaxis requirements endorsed by organizations in the US such as the Joint Commission [25,26].…”
Section: The Importance Of Prophylaxis In Medical Patientsmentioning
confidence: 99%